Virtuous Promises: The Changing Oaths of the Reichshofrat and the Appearance of Impartiality - Peter Roethke (Journal on European History of Law)
As the Imperial Aulic Council of the Holy Roman Empire grew in stature over the course of the early modern period, the integrity of its membership came increasingly into focus. This article analyzes that heightened scrutiny through the lens of oaths. Working from the promulgated versions, drafts, and legislative history of the court ordinances, it argues that the oaths sworn by court officials were specifically tightened in order to deter corruption and the appearance of corruption. The close textual analysis reveals a keen appreciation of bureaucratic mores by the political masters of the court. For such an important instrument of imperial power as the Imperial Aulic Council, perceptions mattered.